2007
DOI: 10.1002/pds.1412
|View full text |Cite
|
Sign up to set email alerts
|

Medication dosing errors in hospitalized patients with renal impairment: a study in Palestine

Abstract: In our study, a wide range of dosing errors was common among patients with renal impairment that was common during hospitalization. Continued medical education in the field of clinical pharmacokinetics is important for physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 17 publications
9
56
4
Order By: Relevance
“…Compared with other studies that evaluated the dosage adjustment according to renal function in inpatient settings, the rate of inappropriate dosages in this study before the intervention (53.0%) was higher than that reported by Salomon et al 17 from France, whose rate was 34.0% of inappropriate dosages, and that by Pillans et al 16 from Australia, who found doses to be inappropriately high in 42.2% of admission prescriptions for drugs that required adjustment. However, it was lower than that reported by Falconnier et al 22 from Switzerland, where doses were not adjusted to individual renal function in 67.0% of renally eliminated drugs before the pharmacist intervention, and by Sweileh et al 18 cept the one by Falconnier et al,22 in which the pharmacist intervention decreased the rate to 19.0%. The previous studies differed in the level of CrCl used for inclusion criteria, the guidelines used, and the hospital units included, which limits the ability to compare the percentages of inappropriate dosages.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Compared with other studies that evaluated the dosage adjustment according to renal function in inpatient settings, the rate of inappropriate dosages in this study before the intervention (53.0%) was higher than that reported by Salomon et al 17 from France, whose rate was 34.0% of inappropriate dosages, and that by Pillans et al 16 from Australia, who found doses to be inappropriately high in 42.2% of admission prescriptions for drugs that required adjustment. However, it was lower than that reported by Falconnier et al 22 from Switzerland, where doses were not adjusted to individual renal function in 67.0% of renally eliminated drugs before the pharmacist intervention, and by Sweileh et al 18 cept the one by Falconnier et al,22 in which the pharmacist intervention decreased the rate to 19.0%. The previous studies differed in the level of CrCl used for inclusion criteria, the guidelines used, and the hospital units included, which limits the ability to compare the percentages of inappropriate dosages.…”
Section: Discussioncontrasting
confidence: 67%
“…Most of the previous studies were descriptive, with no interventions to try to improve the situation. [16][17][18][19] A limited number of studies tried to implement interventions to overcome the problem.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the risk of drug toxicity among patients with reduced renal function, medication doses should be adjusted based on the estimated CrCl, co-morbid disease, and co-prescribed medications. [16] Several recent studies have indicated that dosing errors and the risk of toxicity are common among patients with renal impairment. In agreement with other studies, our results showed widespread dosing errors among patients with renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in keeping with international studies, which found inappropriate dose adjustment in 29 -74% of patients with renal impairment. [2][3][4][5][6][7] Failure to adjust drug doses has several possible explanations. Prescribers might not review renal function results before prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…In renally impaired patients, 29 -74% of drug prescriptions requiring dose adjustment are not appropriately adjusted. [2][3][4][5][6][7] We conducted a retrospective cross-sectional study to determine the prevalence of incorrect dosing of renally eliminated drugs among general medical patients with renal impairment at Groote Schuur Hospital (GSH), Cape Town. We aimed to determine what proportion of drugs prescribed to patients with renal impairment (defined as an eGFR of ≤50 ml per minute per 1.73 m 2 ) in the general medical wards required dose adjustment; and to determine whether drug doses were appropriately adjusted in these patients, using Drug Prescribing in Renal Failure as our reference for dose adjustments.…”
Section: Dosage Adjustment In Medical Patients With Renal Impairment mentioning
confidence: 99%